Questioning the right to be forgotten - Douglas, Michael (Legal Service Bulletin Co-Operative Ltd, 2015)
The Internet has an almost unlimited capacity to remember, which has been described as the problem of ‘digital eternity’. Digital eternity presents a challenge for the protection of the right to privacy. This article questions Europe’s controversial response to that challenge in the so-called ‘right to be forgotten’. Since May 2014, search engine providers like Google have been required to remove thousands of links to personal data upon request. The article identifies the practical and ethical difficulties that come with observance of the right to be forgotten.